2010
DOI: 10.4236/jmmce.2010.91004
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Al6061-SiC and Al7075-Al<sub>2</sub>O<sub>3</sub> Metal Matrix Composites

Abstract: The aluminum based composites are increasingly being used in the transport, aerospace, marine, automobile and mineral processing industries, owing to their improved strength, stiffness and wear resistance properties. The widely used reinforcing materials for these composites are silicon carbide, aluminum oxide and graphite in the form of particles or whiskers. The ceramic particles reinforced aluminum composites are termed as new generation material and these can be tailored and engineered with specific requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(70 citation statements)
references
References 12 publications
1
68
0
1
Order By: Relevance
“…The soft aluminium is reinforced with hard and stiff ceramic particles. The structural aluminium alloys, such as 6xxx and 7xxx series are the most commonly used matrix materials due to their low density and high thermal conductivity [2]. In literature survey, some authors investigated and reported unreinforced alloys that gives less mechanical properties, compared to particulate reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…The soft aluminium is reinforced with hard and stiff ceramic particles. The structural aluminium alloys, such as 6xxx and 7xxx series are the most commonly used matrix materials due to their low density and high thermal conductivity [2]. In literature survey, some authors investigated and reported unreinforced alloys that gives less mechanical properties, compared to particulate reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…Mahendra et al reported a higher tensile strength and hardness for Al-4.5% Cu alloy-fly ash based composites. kumar et al [4] in a study on Al7075-Al 2 O 3 metal matrix composites concluded that the tensile strength properties of composites are found higher than that of base matrix Al7075 alloy and also hardness of the composites increased with increased filler content. Long et al [7] reported the tensile strength of the Al6061-T6 alloy was increased by 20% by the reinforcement with 15 vol% of Al 2 O 3 fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium alloy 6061 possesses very high corrosion resistance and excellent extricable in nature and exhibits moderate strength and finds much applications in the fields of construction like building and highway, automotive and marine applications [4]. The composites formed out of aluminium alloys are of wide interest owing to their high strength, fracture toughness, wear resistance and stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…The Brinell test has frequently used the method to examine the cast samplings [14]. Throughout the assessment tungsten ball indenter with diameter 10 mm by applying load for 10 seconds on five samples with three trails as shown in Table 6.…”
Section: Macro Hardness Test (Brinell Hardness) Astm E10-17 Figure 9:mentioning
confidence: 99%